Analisis Faktor-Faktor Kebijakan Moneter terhadap Pertumbuhan Ekonomi di Indonesia - Amirudin, Ahmad; Soebagyo, Daryono (Nur Science Institute, 2023)
The purpose of this study was to analyze the effect of interest rates, money supply, and inflation on economic growth in Indonesia. The analytical model used is the regression equation using the Partial Adjustment Model method. The type of data used in this study is secondary data in the form of time series data for the period 1999-2019 which is sourced from the World Bank. The results of this study indicate that interest rates affect economic growth in Indonesia, while the money supply and inflation have no effect on economic growth in Indonesia.